IMPROVING THE ACCOUNTING AND INTERNAL AUDIT OF INVENTORY IN BUDGETARY ORGANIZA (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article examines the challenges and opportunities in improving the accounting and internal audit of commodity and material reserves within budgetary organizations. Effective management of reserves plays a key role in ensuring transparency, efficient use of state resources, and prevention of misappropriations. The study highlights theoretical approaches, analyzes current practices, and suggests practical methods for enhancing control, documentation, and internal auditing systems.